On the stability of quadratic double centralizers and quadratic multipliers: A fixed point approach. - Bodaghi, Abasalt; Alias, Idham Arif; Gordji, Madjid Eshighi (Springer Open, 2011)
In the current paper, we prove the superstability of quadratic double centralizers and of quadratic multipliers on Banach algebras by fixed point methods. These results show that we can remove the conditions of being weakly commutative and weakly without order which are used in [8] for Banach algebras.